Do triunfo nos trópicos ao fim da civilização: raça, história e nacionalidade na perspectiva dos intelectuais monarquistas-católicos (1889- 1917) - Flavio Raimundo Giarola (2015)
This thesis analyzes the representations of the nationality of a group of monarchists-Catholics who acted mainly in São Paulo in the late nineteenth century and early twentieth. In the context of symbolic struggles after proclamation of Republic, they developed a national discourse that defended the mestizo roots and the Catholic and monarchist traditions of Brazil. On the other hand, they perceived the present with disappointment, and they believed that only the backcountry people established a remaining link with the lost past. They argued that the militarism, positivism, censorship and violence were intrinsic features of the Republic therefore they devised a possible future only with the advent of a Third Reign, which again would give the country a consistent government with its racial and cultural characteristics.